LAMOST J221750.59+210437.2: A new member of carbon-enhanced extremely metal-poor stars with excesses of Mg and Si. (19th September 2018) - Aoki, Wako; Matsuno, Tadafumi; Honda, Satoshi; Ishigaki, Miho N; Li, Haining; Suda, Takuma; Kumar, Yerra Bharat
Abstract: We report on the elemental abundances of the carbon-enhanced metal-poor (CEMP) star J2217+2104, discovered through our metal-poor star survey with LAMOST and Subaru. This object is a red giant and has extremely low Fe abundance ([Fe/H] = −4.0) and very large enhancement of C, N, and O with excesses of Na, Mg, Al, and Si. This star is a new example of a small group of such CEMP stars identified by previous studies. We find a very similar abundance pattern for O–Zn in this class of objects that shows enhancement of elements up to Si and normal abundance of Ca and Fe-group elements. Whereas the C/N ratio is different among these stars, the (C + N)/O ratio is similar. This suggests that similar abundance ratios of C were also yielded, relative to O–Zn in progenitors, and was later affected by the CN-cycle. By contrast, the heavy neutron-capture elements Sr and Ba are deficient in J2217+2104, compared to the four objects in this class previously studied. This indicates that the neutron-capture process in the early Galaxy, presumably the r-process, has no direct connection to the phenomenon that has formed such CEMP stars. Comparisons of the abundance pattern that are well determined for such CEMP stars with those of supernova nucleosynthesis models constrain the progenitor mass to be about 25  M ⊙, which is not particularly different from the typical mass of progenitors expected for extremely metal-poor stars in general.